Initial Public Offering Timing and Equity Puzzles in Nigeria Capital Market: Evidence from Quoted Small and Medium Scale Enterprises - Hachituru TRIUMPH (IIARD International Journal of Banking and Finance Research, 2026)
The study empirically examines initial public offering and the equity puzzle of quoted small and medium scale enterprises in the Nigerian Capital Market for a period of 3 years from 2022-2024. The equity prices variation in the Nigerian Stock Market and the Nigerian Treasury Bill Rate were used to ascertain the existence or otherwise of equity risk premium puzzle. The equity prices variation was measured as the log of current price index as a ratio of lagged price index of quoted small and medium scale enterprises. The empirical results generally reveal the adjusted R-squared (R2) value is 0.516450 that is 51.6 percent implying that the independent variables The F-statistic value is 5.599440 and its p-value is 0.000009 indicating that the independent variables jointly can impact significantly in equity puzzles of the quoted small and medium scale enterprises of the quoted enterprise firms. The Durbin-Watson reveals that there is no serial correlation in the variables. The beta coefficient of constant is positive with the value of 0.663698 and its p-value is 0.0000 indicating that when all the independent variables are held constant, there will be a positive variation up to the tune of 0.6 units in equity prices puzzles of the quoted SMEs of the quoted enterprise firms and it is significant. Additional, the coefficient value of fixed price initial public offer is 0.080704 band p-value is 0.0000 implying that price initial public offer has a positive coefficient and significant to influence equity prices puzzles of the quoted SMEs. The coefficient value of book building initial public offer is 0.017991 and its p-value is 0.9099 meaning that book building initial public offer is positive and not significant to impact on equity prices puzzles of the quoted SMEs. The Cross-section random effects test comparisons shows that there are significant differences between the fixed and the random effect models. The outcome of the results is therefore rather inconclusive, suggesting that generally long run co-movements cannot be established between initial public offering and Equity Risk Premium. Thus, the Equity Risk Premium cannot be confirmed in the study in Nigeria. The study recommends, among others, that appropriate policy that will take into account these differences in investors’ preferences should be vigorously pursued.